Achieving Diversity and Inclusivity in the Wider Educational Context : Enhancing General Staff Capacity to Provide Services to a Diverse Student Body : Final Report for a 1998 Staff Development Grant. - Black, Barbara; Callander, Maureen (Committee for University Teaching and Staff Development, 2000)
This is the final project report for a 1998 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The project was designed to: raise staff members' awareness and knowledge of diversity and inclusivity issues within the wider educational context of service provision; increase staff members' competence in inclusive communication practices including cross-cultural communication; increase staff groups' competence in designing and implementing more inclusive administrative and organisational practices; develop guidelines on appropriate practices. The report summarises the project and provides justification for its development, and evaluates its effectiveness.